Secondary Mathematics Knowledge in Econometrics - Trung, Lê Thái Bảo Thiên (VNU Journal of Science: Education Research, 2015)
Econometrics (economic measure) can be defined as a social science in which economic and mathematical knowledge are co-present in the analysis of economic phenomena. Knowledge already taught in secondary mathematics education must be transformed into tools for modeling phenomena of economic in reality. In this paper, we are going to explain the difficulties of students when they have to mobilize the two objects of knowledge: the slope of the straight line and the logarithms. Keywords: Mathematics knowledge in secondary education, slope of the straight line, logarithm, econometrics.